Rehabilitation Effects of Fatigue-Controlled Treadmill Training After Stroke: A Rat Model Study - Xu, Yuchen; Yao, Yuanfa; Lyu, Hao; Ng, Stephanie; Xu, Yingke; Poon, Wai Sang; Zheng, Yongping; Zhang, Shaomin; Hu, Xiaoling (Frontiers in Bioengineering and Biotechnology, 2020)
Background Traditional rehabilitation with uniformed intensity would ignore individual tolerance and introduce the second injury to stroke survivors due to overloaded training. However, effective control of the training intensity of different stroke survivors is still lacking. The purpose of the study was to investigate the rehabilitative effects of electromyography (EMG)-based fatigue-controlled treadmill training on rat stroke model.Methods Sprague-Dawley rats after intracerebral haemorrhage (ICH) and EMG electrodes implantation surgeries were randomly distributed into three groups: the control group (CTRL, n=11), forced training group (FOR-T, n=11), and fatigue-controlled training group (FAT-C, n=11). The rehabilitation interventions were delivered every day from Day2 to Day14 post-stroke. No training was delivered to the CTRL group. The rats in the FOR-T group were forced to run on the treadmill without rest. The fatigue level was monitored in the FAT-C group through the drop rate of EMG mean power frequency (MPF) and rest was applied to the rats when the fatigue level exceeded the moderate fatigue threshold. The speed and accumulated running duration were comparable in the FAT-C and the FOR-T groups. Daily evaluation of the motor functions was performed by the modified Neurological Severity Score (mNSS). Running symmetry was investigated by the symmetry index (SI) of EMG bursts collected from both hindlimbs during training. The expression level of neurofilament-light (NFL) in the striatum were measured to evaluate the neuroplasticity.The FAT-C group showed significantly lower mNSS compared to the FOR-T (P≤0.003) and CTRL (P≤0.003) groups. The FAT-C group showed a significant increase on the symmetry of hindlimbs since Day7 (P=0.000) while the FOR-T group did not (P=0.349). The FAT-C group showed a higher concentration of NFL compared to the CTRL group (P=0.005) in the unaffected (UN) striatum and the FOR-T group (P=0.021) in the affected (AF) striatum.The treadmill training with moderate fatigue level controlled was more effective in motor restoration than forced training. The fatigue-controlled physical training also demonstrated positive effects in the striatum neuroplasticity. This study indicated that protocol with individual fatigue-controlled training should be considered in both animal and clinical studies for better stroke rehabilitation.